2017
DOI: 10.5005/jp-journals-10024-2157
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices regarding Pharmacovigilance and Adverse Drug Reaction reporting among Dental Students in a Teaching Hospital, Jodhpur, India: A Cross-sectional Study

Abstract: Introduction: This is a cross-sectional knowledge, attitude, and practices (KAPs) study on pharmacovigilance (PV) and adverse drug reaction (ADR) reporting among dental students in a teaching hospital in India. Aim:The aim of this study was to assess the KAP of dental students regarding PV, ADR reporting, and barriers toward the same. Materials and methods:A cross-sectional survey using a selfadministered, investigator-developed, close-ended questionnaire was conducted in an academic dental hospital in India. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This was in accord with the study conducted by Aldaij M et al . [ 17 ] who also concluded that overall health- related students show better knowledge and attitudes towards their aesthetic dental treatments and needs.…”
Section: Discussionmentioning
confidence: 99%
“…This was in accord with the study conducted by Aldaij M et al . [ 17 ] who also concluded that overall health- related students show better knowledge and attitudes towards their aesthetic dental treatments and needs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that evaluated pharmacovigilance knowledge, attitude or perception of healthcare students started to appear since 2011. The majority of the included studies involved pharmacy students [11][12][13][14][15][16][17][18][19], while few studies specifically focused on healthcare students [20][21][22], nursing students [23], and dental students [24,25]. The total number of included studies was twenty-nine, with sample sizes ranging from 30 to 874.…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%
“…Attitude towards pharmacovigilance and ADR reporting was measured using multiple-choice response options ranging from 2 to 5 questions [20,30], and using a 5-point Likert scale [16,24]. Although only a few studies evaluated attitude; it should be noted that some questions used were related to measuring the perception rather than attitude [16,22,26,31].…”
Section: Pharmacovigilance Attitudementioning
confidence: 99%
See 1 more Smart Citation
“…Hence results of the current study should be inferred cautiously and not be globalized. Definite intervention planning cannot be done by merely cross-sectional studies; however a good stage for future answers is provided by such studies [ 17 ].…”
Section: Discussionmentioning
confidence: 99%